Fasting enhances growth hormone secretion and amplifies the complex rhythms of growth hormone secretion in man. - Ho, K Y (1988)
Studies in man have shown that the episodic release of growth hormone (GH) is infrequent and erratic, and unlike that in the rat does not appear to have discernible ultradian periodicities. However, these observations in nonfasted subjects may be invalid since mixed nutrients have unpredictable effects on GH release. Moreover, in the fed state basal GH levels are frequently undetectable, thus rendering the identification of low amplitude pulses unreliable. Accordingly, the 24-h pulsatile pattern of GH secretion obtained from repetitive venous sampling in six normal adult male subjects was examined during a control fed day and during the first and fifth days of a 5-d fast. The GH data were analyzed using two distinct methods: a discrete pulse detection algorithm (Cluster analysis) and Fourier expansion time-series, which allows fixed periodicities of secretory activity to be resolved. The 5-d fast resulted in a significant increase in discrete GH pulse frequency (5.8 +/- 0.7 vs. 9.9 +/- 0.7 pulses/24 h, P = 0.028), 24 h integrated GH concentration (2.82 +/- 0.50 vs. 8.75 +/- 0.82 micrograms.min/ml; P = 0.0002), and maximal pulse amplitude (5.9 +/- 1.1 vs. 12.3 +/- 1.6 ng/ml, P less than 0.005). While multiple low-amplitude sinusoidal periodicities were present on the control fed day, time-series analysis revealed enhancement of circadian and ultradian cycles on the first and fifth days of fasting. Concomitantly, fasting resulted in a decline (day 1 vs. day 5) in serum concentrations of somatomedin C (1.31 +/- 0.22 vs. 0.77 +/- 0.18 U/ml) and glucose (4.9 +/- 0.2 vs. 3.2 +/- 0.2 mmol/liter), and a marked rise in free fatty acid (0.43 +/- 0.12 vs. 1.55 +/- 0.35 mmol/liter) and acetoacetate (35 +/- 6 vs. 507 +/- 80 nmol/liter). We conclude that the acute nutritional status is an important determinant of spontaneous pulsatile GH secretion in man. Fast-induced enhancement of GH release is achieved through combined frequency (discrete pulses) and amplitude (sinusoidal periodicities) modulation. Such alterations in somatotropic hormone release may play an important role in substrate homeostasis during starvation.